Proximate Study and Acceptance of “Abon Ikan” Using Different Fish Meats in Cilacap - khoeruddin wittriansyah; Ari Kristiningsih; Annas Setiawan Prabowo (Universitas Djuanda, 2021)
Cilacap is a center of fisheries in Central Java province. One of the development fisheries product is the processing of “Abon Ikan”. The advantage of “Abon Ikan” “Abon Ikan” is they have a long shelf life and can give additional income for fishermen. Different fish meat will affect the taste and nutritional content of the “Abon Ikan”. This study aims to analyze the differences in “Abon Ikan” from 3 types of fish meat used in Cilacap. The fish meat used is tuna, catfish (clarias), and patin (pangasius). The three “Abon Ikan” products were then analyzed for their nutrient contents using proximate analysis. Acceptance test using the sensory test carried out on 50 respondents covering aspects of taste, aroma, texture, and appearance. Based on the results of the proximate analysis, three parameters were in accordance with SNI Abon Ikan (1995) are crude protein content, ash content, and crude fat content. Parameters of water content and crude fiber content have not in accordance SNI Abon Ikan. “The hedonic test for acceptance of the four categories: taste, aroma, texture, and appearance, the highest positions were all in the Abon patin (4.04., 3,7., 4.02., 3,92).